A importância das habilidades sociais para o processo de adaptação de imigrantes residindo no Brasil - Lozano, Angélica Maria Bossa (2022)
Even now, in the 21st century, millions of people around the world are leaving their country of birth, each year. However, each immigrant must negotiate a complex process to adapt to the new sociocultural context that exists in the country of arrival. The difficulties and errors that occur in interpersonal interactions can pose a risk for the mental health of the immigrant. In addition to needing to learn a new language to communicate with people from the host country, immigrants need to adapt the use of social skills, learned in their country of origin, to the local culture. However, immigrants’ existing repertoire of social skills, even if developed in a different cultural context, may function as a protective factor, contributing to a more positive and less stressful adaptation process. Given the lack of empirical information on these issues, the objective of this study was to examine immigrants’ perceptions of the importance of the use of social skills during the initial phase of the adaptation process. For this purpose, a sample of 40 immigrants was recruited: (a) over 18 years of age, (b) residing in Brazil, (c) with a reasonable (or higher) level of reading comprehension in Portuguese and (d) with access to technological resources, to answer a questionnaire via Google Forms. Participants answered questions about their use of 10 classes of social skills. In addition to observing the percentage of immigrants who indicated that they used each class of skills during the first months after their arrival in Brazil, a qualitative analysis of the examples they gave was performed, to verify whether they were able to: (a) achieve their goals, (b) maintain or improve their self-esteem, (c) maintain or improve the quality of their (new) relationships, (d) meet their our own needs while responding to the needs of others and (e) act in accordance with the code of human rights. As key results, the most commonly used class of social skills was "support" (100% of the participants indicated that they used these skills) and the least frequently used was "communication" (57.5%). The examples the participants gave indicated that, in addition to achieving their goals, the use of each class of social skills almost always contributed to the formation of good quality relationships. However, the sample included many people from a university context, who may be different from immigrants who have suffered traumatic experiences in their home country that could lead to difficulties interacting with others. Considering the relevance of the repertoire of social skills of the participants for their successful sociocultural adaptation, research with refugees is recommended, both to evaluate their repertoire of social skills, as well as to evaluate the possibility of helping them in the use of this repertoire in Brazil, to favor their positive integration in Brazilian society.